UNIVERSITY MANAGEMENT: IDENTIFICATION AND ANALYSIS OF INDICATORS USED IN LITERATURE - Nuernberg, Enrique Gomes; Ensslin, Sandra Rolim; Cardoso, Thuine Lopes; Valmorbida, Sandra Mara Iesbik (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study aimed to analyze the indicators used in the literature to evaluate the university management. National and international scientific publications were selected through ProKnow-C, in the period 1987-2015, and identified the existence of 24 articles (11 national and 13 international), which addressed the university management using performance indicators. This is a descriptive study with a qualitative approach. The results show: (i) a total of 354 indicators (80% in the literature), grouped into four dimensions; (ii) 83% measure non-financial aspects; (iii) management accounts for 42% of the indicators predominating financial aspects; (iv) teaching concentrates 33% of the indicators, with most of the non-financial aspects; (v) the extension dimension is represented by a few indicators, especially in the national literature; (vi) most indicators of research involves measuring the dissemination of research; and (vii) there is a lack of indicators to monitor the realization of organizational strategies and that give account to judge the achievement of the goals set by universities.